Jane Eyre: do romance (1847) ao filme (2011) - Nascimento, Sandra Mônica do (2014)
This dissertation aims to investigate how the Charlotte Brontë s literary project presents in the novel, Jane Eyre (1847), through female authorship, and, as its transposition into Cinema, the movie version by Cary Joji Fukunaga´s Jane Eyre (2011) occurs. The literary project of the author focuses on the issue of gender and its concern was to give voice to the women of her time. The director´s project for this movie comes from melodrama to the triumph of love search. The purpose of analysis is to understand how the interpretation of this source-novel occurs in the 21st century, with the aim of examining how this story is reread, seeking current interpretive understanding of the novel through the film. Thus, this study will demonstrate the importance of the periodization as proposed by Jameson (1992) for the reading of the novel and its transcreation, according to Campos (2004), considering the relationship between economic s, political, social and aesthetic characteristics of each period, as also teaches Candido (1967). The research was developed through the reading the novel, of the theoretical works about the author as well as the director and analysis of filmic narrative.